Sosialiasi Cyber Hating Pada Pemuda Ichwan di Kampung Cireungit, Samarang Garut - Nurul Irpan; Reynaldi Fahreza; Gugum Rahmat G; Hilman Syahril; Rio Adhitya R; Ilham Abdul G; Fachrry A R (Jurnal Pengabdian Literasi Digital Indonesia, 2022)
The development of today's era is very fast, technology has now become part of our lives, for example, social media is now the virtual world has really become the second environment of humans. Freedom of speech is indeed good but sometimes the freedom of speech is sometimes too excessive and even contains elements of suffrage that harm individuals or groups. So that RTIK is now holding a Movement to socialize the dangers of hate speech on social media. By giving a post test to see the results of the material presented whether the material can be absorbed by the person receiving the information or not. The arithmetic team carried out socialization to the mosque community/organization, namely Pemuda Ichwan to convey the dangers of hate speech.